Dampak Peningkatan Kunjungan Terhadap Pendapatan Pedagang Makanan dan Minuman di Danau Kampung Bintaro Pesanggrahan, Jakarta Selatan - Ratnaningtyas, Heny; Ingkadijaya, Rahmat; Habibie, Fachrul Husain (Tourism Scientific Journal, 2024)
This research aims to determine the influence of the strategic location of Lake Kampung Bintaro Pesanggrahan on the increase in the number of tourists, as well as evaluate the impact on the income of food and beverage traders in the area. This type of research is qualitative research with research methods using direct observation, in-depth interviews, and literature study. The research results show that visitors frequently visit Kampung Bintaro Lake on weekends because of its strategic location and facilities, such as places of worship, culinary delights, entertainment, and unique experiences. This impacts small traders in meeting visitors' needs for food and drinks. Beverages, thereby helping small traders increase their income. Lake Kampung Bintaro Pesanggrahan, as a strategically located tourist destination, has great potential to attract more tourists and positively contribute to the income of food and beverage traders. Visitors are advised only to throw rubbish carefully. The DKI Jakarta government is always expected to maintain the lake's condition well, such as cleaning the lake of rubbish, maintaining water quality, and keeping the lake ecosystem whole to remain healthy and function well. Food and beverage traders in Lake Pesanggrahan are encouraged to prioritize the cleanliness of food and beverages and the surrounding environment to maintain customer health and preserve nature.